TINGKAT KESIAPAN GURU DALAM PELAKSANAAN PEMBELAJARAN BERDIFERENSIASI PADA KURIKULUM MERDEKA DI SEKOLAH DASAR SE-KECAMATAN KEMIRI - FATINA NISA NASTITI PUTRI; Riawan Yudi Purwoko; Suyoto (STKIP Subang, 2025)
This study aims to determine the level of readiness of elementary school teachers in planning, implementing, and evaluating differentiated learning. This type of research is quantitative research with a survey approach, where the data collection technique uses a questionnaire, which will then be analyzed descriptively. The results of the study show that the mean value of the indicator for mapping students' learning needs in the learning planning section is 3.51 (High), meaning that teachers have a good understanding of differentiated learning planning. The indicator for the learning implementation process is in the